Profiling Analysis of Volatile and Non-volatile Compounds in Vitis Vinifera Berries (cv. Chardonnay) and Spontaneous Bud Mutation - Zheng, Ting; Zhang, Saihang; Leng, Xiangpeng; Sadeghnezhad, Ehsan; Li, Teng; Pervaiz, Tariq; Liu, Fanqi; Jia, Haifeng; Fang, Jinggui (Frontiers in Nutrition, 2021)
A novel clonal variety of Vitis vinifera was identified from ‘Chardonnay’ using inter-simple sequence repeat (ISSR) markers and called ‘Bud mutation’. The metabolomic profiles in Chardonnay and Bud mutation berries, indicated essential differences in the expression of key genes in the pathways of 2-C-methyl-D-erythritol-4-phosphate (MEP) and lipoxygenase-hydroperoxide lyase (LOX-HPL). Bud mutation fruits also matured 10 days earlier than Chardonnay and was higher in carotenoids, sugars, and acidic compounds. Furthermore, the gene expression was examined in the biosynthetic pathways of two ripening-associated hormones, abscisic acid (ABA) and jasmonic acid (JA), that significantly increased in Bud mutation compared to Chardonnay fruit. The synthesis and metabolism of amino acids, terpenes, fatty acids, volatile components, and specialized metabolites significantly increased in Bud mutation. Therefore, in comparison with Chardonnay, Bud mutation is considered a highly aroma-producing grape variety for improvement in the beverage industry.